From Cosmopolitanism Islam to Colonial Hegemony: Rereading the Social History of the Aru Islands as the Economic Base of Eastern Indonesia - Sahradad, Herdi; Wing Artha, Gratia (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
This article explores the traces of cosmopolitanism and Islamic colonialism in the Aru Islands, Maluku (Moluccas) which took place several centuries ago. Also depicts the social history of the Aru Islands, Maluku, in the map of Indonesia's national history. In the era of Southeast Asian trade, the Aru Islands have long been fostered under a very open, cosmopolitan and dynamic Islamic authority where trade and migration are the daily dynamics of the people in this very exotic and rich archipelago. Islam continues to spread to Papua from the Aru Islands, which proves how strong the resilience of the island's people is. Changes occurred when the West colonial powers entered the islands until finally there was a physical conflict in the form of war. Because they did not prepare themselves, the Muslims here lost and were thrown to other islands while continuing to struggle against the West colonial powers. Colonialism increasingly instilled its power and spread a religion (Christian) that was different from Islam (the general belief) held in the Aru Islands. This Western colonialism created complex dynamics, where trade on the one hand was increasingly bustling, but colonial hegemony over the Aru islands was also very real and sharp and shrouded in physical conflict between the Aru Islands Muslims and European colonialists.